Analisis Kebijakan Penjualan Senjata Militer Donald Trump ke Arab Saudi - Muhamad Rachmat Hidayatullah; Fendy Eko Wahyudi (Journal of International Relations Diponegoro, 2019)
This study aims to find out why Donald Trump ignored the congress in selling weapons to Saudi Arabia. The majority of the congress wants Trump to stop selling his weapons to Saudi Arabia because of controversies about Saudi Arabia such as ignoring human rights in the Yemen conflict and the possible role of the Saudi government in killing Jamal Khashoggi, a Saudi journalist. This study uses poliheuristic theory and qualitative methods in analyzing. In poliheuristics, leaders will eliminate alternative choices that are not in accordance with their noncompensatory principles. In general, the noncompensatory is a choice that does not harm the domestic political status, but the principle of noncompensatory can differ between leaders. An influential factor is the character of the leader in determining foreign policy which causes leaders to tend to fight their political constraints. The results of this study are that Trump has a task-oriented leader character and has high confidence in his ability to cope with events. This character influenced his foreign policy making to ignore his political obstacles, so Trump dared to make the decision to continue selling military weapons without congressional approval.